(untitled) (TAJ: Journal of Teachers Association, 2018)
Background: Studies of the impact of mental disorders on educational attainment are rare. Mental disorders, those beginning in childhood or adolescence may increase the risk of early droup out from education. The latter has been shown to have adverse life-course consequences on individuals such as greater demand on social welfare entitlements. Objective: To find out socio-demographic status and psychiatric comorbidity profile of patients with education droup out. Design: Descriptive cross sectional study. Setting: All cases were selected from patients attending at Comilla Medical College hospital and Tertiary Care hospitals in Comilla City from August 2014 to April 2015. Methods: A total of 50 droup out patients aged 10 to 30 years who fullfiled the enrolment criteria included in the study. A semi structural questionnaire, DSM-5 and ICD-10 have been used as research instruments. The Frequency tables, summary tables and appropriate graphs were prepared to describe the population characteristics and study finding. Result: Total 62 participants were approach for interview. Considering inclusion and exclusion criteria finally 50 patients were selected for the study. In this study, anxiety disorders was 8%, behaviour/ impulse control disorders was 8%, mood disorders was 16%, substance use disorders was 24%, schizophrenia spectrum disorders was 12% and composite psychiatric disorders was 32%. Among droup out patient’s non- completion of primary education was 14%, non- completion of secondary education was 20%, non- completion of higher secondary education was 24%, not entry to tertiary education was 12% and non- completion of tertiary education was 30%. Among behaviour/impulse control disorders non- completion of primary education was 6%, substance use disorders non- completion of higher secondary education was 10%, mood disorder both non- completion of higher secondary education and non- completion of tertiary education were 6%. Among composite psychiatric disorders non- completion of secondary education, non- completion of higher secondary education and non- completion of tertiary education were 8%, 6% and 12% respectively. Socioeconomic status represented the homogenous result in this study. Most of the psychiatric morbidity was male (62%) and age group of 18-24 years (54%). Conclusion: Onset of mental disorder and subsequent droup out from education that was found in this study. Further multi-centered prospective and population-based studies should be desined to fint out the exact situation. TAJ 2013; 26: 38-42